Implementation of Problem-Based Learning Model to Enhance Critical Thinking Skills on Force Material in Fourth Grade Elementary School. - Reza Maulana; Endang Susilaningsih; Bambang Subali (Universitas Negeri Semarang, 2022)
Learning about force material in natural science can be challenging for elementary school-age children due to its abstract nature. This poses a problem in the learning process, as force is essentially a concept that exists only in the human mind. The purpose of this study was to investigate the impact of the Problem-Based Learning (PBL) model on enhancing critical thinking skills in fourth-grade elementary school students, specifically in the context of force material. The study employed a quantitative experimental method (quasi-experimental) and involved a total sample of 50 students from SDN Tipar Bogor. The independent variable in this study was the utilization of the Problem-Based Learning model, while the dependent variables were the students' critical thinking ability and mastery of the minimum competency in force material. In this study, the data collection techniques were tests and observation. The results of the study revealed a significant difference in the average critical thinking ability of the experimental class, which was found to be 85.06. This indicates that the students in the experimental class successfully met the specified target, surpassing the minimum completeness criterion of 70. Based on the findings, it can be concluded that the implementation of the Problem-Based Learning (PBL) model significantly improved students' critical thinking skills in the context of force material. The control class achieved an average score of 75.08, meeting the minimum mastery criterion of 70. This indicates that the PBL model was effective in enhancing students' critical thinking abilities. The N-Gain results demonstrated a substantial increase of 0.75 in the experimental class, which falls under the high gain category. The obtained results can serve as a valuable reference for implementing the Problem-Based Learning (PBL) model in science education, particularly in teaching force material to elementary school students. The study suggests using the Problem-Based Learning (PBL) model for teaching force material to elementary school students. It effectively enhances critical thinking skills and is recommended for science education in elementary schools.